JENIS PAKAN OWA JAWA (Hylobates moloch Audebert, 1798) DI TAMAN NASIONAL GUNUNG HALIMUN SALAK PROVINSI JAWA BARAT - Hadi Surono (Universitas Sultan Ageng Tirtayasa, 2015)
Javan gibbon (Hylobates moloch) is one of Javan endemic primates. Gunung Halimun Salak National Park is one of its suitable habitat that supports significant number of population of the gibbon in Java. One of the habitat usage by Javan Gibbon is for foraging at tree canopies.. This study aimed to reveal food plants for feeding. This study was conducted at Cikaniki Research Station, Citalahab village and the surrounding habitats. The equipments used in this study included binocular, range finder, camera, stop watch, ribbon, compass, tally sheet, rope, work map, and stationary. This study was focussed on two groups of Javan gibbon consisting 4 and 3 individuals respectively.. The data collected using focal animal sampling with continous recording and scan sampling methods.. Javan gibbon consumed 47 kind of feeds covering 46 species of plants and one species of insect. Parts of the plants eaten by the Javan gibbon were fruits, leaves, and flowers representing 77,8% , 21,02% , 1,18% respectively. The Javan gibbon was also observed eating insects which was 0,002% of the total consumption.